On Some Challenges in Drawing the Allocation Under Several National Legal Acts - Glushkova, Maria (Yearbook of the Law Department, 2022)
A properly drafted and enforced allocation is the culmination of a legal dispute. It puts an end to the dynamically evolving civil legal relations through the expected fair statutory satisfaction of all creditors. The activity of drafting allocations under the relevant national legal provisions is quite underrated and little known among legal practitioners in Bulgaria. The legal doctrine lacks a thorough and comprehensive study of the subject and the case-law is extremely controversial. These circumstances give rise to a need to explore and present the subject in its comprehensiveness and completeness in the present study.